2015
DOI: 10.4018/ijwsr.2015040101
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent QoS Aware Best Service Combination Selection

Abstract: Service Oriented Architecture allows developing complex business applications from existing services. Given that many services are available with the same functionality and with different Quality of Service (QoS) attributes, one common challenge is to select the best service combination regarding user's requirements. Existing solutions often consider static QoS values for candidate services. Nevertheless, in real world applications, QoS values can change during time. In addition, besides structural constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Hence, a near-tooptimal solution can be found more quickly. In our previous work [6], we demonstrated that the computation time of the pruning process is equal to 23 ms in the worst case. This is an expected result since the computation of the different QoS and temporal local thresholds can be applied in parallel.…”
Section: B Experimental Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Hence, a near-tooptimal solution can be found more quickly. In our previous work [6], we demonstrated that the computation time of the pruning process is equal to 23 ms in the worst case. This is an expected result since the computation of the different QoS and temporal local thresholds can be applied in parallel.…”
Section: B Experimental Resultsmentioning
confidence: 89%
“…1) Constraints Specification: A composed service is usually specified as an abstract business process. Each business process is composed by a set of activities or abstract tasks A = {A 1 , ..., A n } which depend on each other by a set of structural dependencies that can follow different patterns including sequential, parallel, choice and loop patterns [6]. In addition to structural constraints, business designers can also require supplementary intra and inter-task temporal constraints at the business level in order to increase their market share and profitability.…”
Section: Service Selection Problemmentioning
confidence: 99%
See 3 more Smart Citations